A study to determine the severity based outcome of pediatric patients with dengue spectrum disorders in a tertiary care hospital - M., Vijaysuryakiran K.; Pattar, Mounesh; Paida, Sanjay (International Journal of Contemporary Pediatrics, 2019)
Background: Dengue Fever (DF) has become a major global public health problem. The majority of dengue viral infections are self-limiting, but complications may cause high morbidity and mortality. Dengue infection ranges from mild illness to a severe form of haemorrhagic fever and shock syndrome which may prove fatal. Objective of the study was to determine severity-based outcome in children with dengue spectrum disorder in a tertiary care centre in Mumbai. Methods: It was a prospective, non-interventional, observational, surveillance study conducted over 14 months (from September 2016 till October 2017). Children aged <18 years admitted to Nanavati Super Specialty Hospital, Mumbai diagnosed with dengue spectrum disorders according to WHO 2009 classification with clinical features and laboratory investigation confirming dengue were enrolled as study participants. Results: Out of 127 patients, 57(44.9%) were females and 70(55.1%) were males. 81(63.8%) were ward patients, 46(36.2%) required PICU admission. 17(13.4%) patients had dengue with warning signs, 100(78.7%) had dengue without warning signs and 10(7.9%) had severe dengue according to WHO 2009 case classification of dengue. 122(96.1%) were discharged home, 4(3.1%) died of dengue and dengue related complications all four deaths occurred in children with severe dengue. Conclusions: This study showed that commonest inpatient admission category among children with dengue according to WHO 2009 classification was dengue without warning signs Overall mortality in patients with dengue fever without warning sign as well those with warning sign remains very low. Children presenting with severe dengue associated with either organ failure or refractory shock are at increased risk of mortality.